Anglo-Norman castles and religious foundations in Counties Louth and Down : a comparison with examples in England and Wales - Lennon, Alison (Trinity College (Dublin, Ireland). Department of History, 2009)
This aim of this thesis is to prove that in the aftermath of the Anglo-Norman invasion of Ireland in 1169, the buildings constructed by the first wave of settlers reflected the architectural influences of contemporary buildings which they were familiar with on the their homelands in England and Wales. Proving this will require an archaeological analysis of specific castles and religious foundations built by these Anglo-Norman settlers in Counties Down and Louth, in an attempt to find evidence of these influences. This research will study particular Anglo-Norman families, focusing on those who had the most influence during the initial decades after the invasion. It is presented as a multi-disciplinary view of the subject, as it is necessary to examine the historical background of each of the Anglo-Norman settlers in order to ascertain exactly where they were based in England, and therefore exactly which castles and religious foundations they would have been familiar with. Rather than a brief overview of all the monuments constructed by particular Anglo-Norman lords in both counties, this research will provide a detailed examination of the archaeology of specific castles and religious foundations.
Keywords: Medieval History, Ph.D.; Ph.D. Trinity College Dublin.